Using a Serious Game to Train Violence Risk Assessment and Management Skills. (April 2019) - Mason, Jonathan; Loader, Krystelle
Background. Staff in healthcare andhuman services settings are frequently exposed tointerpersonal violence and challenging behaviour that requires competence in assessing and managing the associated risks. The pressure to adequately manage these risks can result in high levels of workplace stress. Intervention. Students and workers face many barriers to receiving practical training inrisk assessment and management, and serious gaming has shown promise as a method of learning in a realistic, experiential, and safe environment. This study examined whether a serious game was an effective and engaging method for training people to assess and manage challenging behaviours, compared to a traditional mode of learning. Method. The 78 participants in this quasi-experimental study were divided into a serious game condition and a traditional learning condition. Participants were scored on their acquired knowledge across five categories and surveyed on their level of engagement in the learning method. Results. Results demonstrated no significant differences between learning conditions on acquired knowledge, and significantly higher levels of engagement in theserious game condition. Conclusion. Serious games may offer an effective way of teaching risk assessment and management skills to novice healthcare professionals. As an engaging, cost-effective, authentic, flexible, and self-directed learning method, the advantages of utilising serious gaming as a training tool in healthcare and human services are substantial.